Antibiotic residues in milk from small dairy farms in rural Peru. - Redding, L.E. (2014)
The use of antibiotics in livestock can pose a public health threat, especially if antibiotic residues remain in the food product. Understanding how often and why farmers sell products with antibiotic residues is critical to improving the quality of these products. To understand how often milk with antibiotic residues is sold on small farms in a major dairy-producing region of Peru and identify factors associated with selling milk with antibiotic residues, we tested milk samples for antibiotic residues from every provider on three routes of commercial milk companies and from bulk tanks of farmers currently treating cows with antibiotics. We also asked farmers if they sold milk from treated cows and examined factors associated with the tendency to do so. The prevalence of milk contamination with antibiotic residues on commercial routes was low (0–4.2%); however, 33/36 farmers treating their animals with antibiotics sold milk that tested positive for antibiotic residues. The self-reported sale of milk from treated cows had a sensitivity, specificity, and positive and negative predictive values of 75.8%, 100%, 100% and 27.2%, respectively (with testing of milk for residues as the gold standard). Finally, 69/156 randomly selected farmers reported selling milk from treated cows, and farmers’ knowledge of antibiotics and the milk purchaser were significantly associated with a farmer’s tendency to report doing so. Educating farmers on the risks associated with antibiotics and enforcement of penalties for selling contaminated milk by milk companies are needed to improve milk quality.